Tax Policy Changes, Tax Revenue and Budget Deficit: A Case in Sri Lanka - Anojan, V. (Jaffna University International Research Conference, 2014)
The aimof Tax Policy Changes, Tax Revenue The aim of the tax policy changes are generating and increasing the tax revenue of the country. The high tax revenue can reduce the budget deficit of the country. There are number of tax policy changes have been made by Sri Lanka despite some on-going economic issues. Therefore, this study presents a new model of tax policy changes, tax revenue and budget deficit. Quantitative approach was utilized in this study to analyse tax policy changes, direct tax revenue, indirect tax revenue and budget deficit of the country. This study covers 23 years which are from 1990 to 2012 in Sri Lanka. According to the quantitative study the impact of tax policy changes on the tax revenue of the country in the high level (P < 0.01) however tax policy changes have not significant impact on budget deficit of the country. Further, direct tax revenue of Sri Lanka has significant impact on the budget deficit (P < 0.05) and predicts 98.9% of the variation found. There is a mean difference in tax revenue and budget deficit between the period of tax policy changes years and no tax policy changes years even though there is no significant mean difference. The tax revenue of the country was higher in the years of tax policy changes than no tax policy changes years. Correlation analysis confirmed that there is significant relationship between tax policy changes and tax revenue as well as budget deficit of the country. Also the direct tax revenue and indirect tax revenue have the significant relationship with budget deficit of the country.
Keywords: Direct Tax Revenue; Indirect Tax Revenue; Tax Policy Changes